2016
DOI: 10.1016/j.janxdis.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of targeting tolerance of children’s negative emotions among anxious parents of children with anxiety disorders: A pilot randomised controlled trial

Abstract: HighlightsParent-delivered CBT is effective for child anxiety when parent is also highly anxious.Little evidence that improvements in parent tolerance are associated with treatment gains.Adjunct treatment to target parent’s tolerance may not be necessary.Tolerance improves as child anxiety improves, even if not targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…Emerson et al (unpublished) demonstrated that improvements in parental experiential avoidance following a mindfulness-based parenting intervention uniquely predicted improvements in child internalizing problems. In contrast, a pilot randomized controlled trial of a tailored parent intervention targeting parental distress tolerance, Hiller et al (2016) reported no differences in child anxiety outcomes compared to standard behavioral parenting intervention. Hiller et al (2016) did report differential effects on positive parenting and the quality of the parent–child relationship, with increases for those in the targeted treatment condition, and decreases for those in the standard condition.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Emerson et al (unpublished) demonstrated that improvements in parental experiential avoidance following a mindfulness-based parenting intervention uniquely predicted improvements in child internalizing problems. In contrast, a pilot randomized controlled trial of a tailored parent intervention targeting parental distress tolerance, Hiller et al (2016) reported no differences in child anxiety outcomes compared to standard behavioral parenting intervention. Hiller et al (2016) did report differential effects on positive parenting and the quality of the parent–child relationship, with increases for those in the targeted treatment condition, and decreases for those in the standard condition.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, a pilot randomized controlled trial of a tailored parent intervention targeting parental distress tolerance, Hiller et al (2016) reported no differences in child anxiety outcomes compared to standard behavioral parenting intervention. Hiller et al (2016) did report differential effects on positive parenting and the quality of the parent–child relationship, with increases for those in the targeted treatment condition, and decreases for those in the standard condition. The question remains whether targeting parental experiential avoidance within parenting interventions may or may not indicate improvements in child outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…When it comes to parental anxiety, it remains unclear exactly how best to improve child outcomes (e.g. Hudson, Newall, Rapee, et al, 2014), although recent studies indicate that good outcomes can be achieved when parents are supported as part of, or alongside, their child's treatment (Creswell et al, 2020;Hiller et al, 2016).…”
Section: What Should We Deliver To Whom?mentioning
confidence: 99%
“…PLTA models are characterized by parents implementing a structured, evidence-based treatment protocol independently at home while receiving limited assistance from a trained therapist. Studies on PLTA treatment for anxiety [27][28][29][30][31][32][33][34][35][36] have yielded promising results. Notably, one study 34 comparing treatment responses of varied CBT delivery formats targeting anxiety in a pooled sample of typically developing youth (n=1,253) found no significant differences between therapist-led individual or group treatment and PLTA interventions (except for primary specific phobia, where therapist-led individual treatment was superior).…”
Section: Parent-led and Stepped-care Interventionsmentioning
confidence: 99%
“…Matching treatment to families and individual patients' needs, and tailoring subsequent treatment, may be an efficient and effective approach consistent with parents' desire to help their child. Previous studies on PLTA treatment for anxiety [27][28][29][30][31][32][33][34] and recent stepped-care trials for childhood anxiety [38][39][40] provide strong preliminary evidence to support the advancement of testing stepped-care models for internalizing symptoms among youth. Together with the substantial impairment associated with clinical anxiety in individuals with ASD across the age span, [13][14][15] this provides a strong rationale for the use of a parent-led, flexible, individually-tailored cognitive-behavioral intervention for anxiety in youth with ASD.…”
Section: Innovations Of the Parent-led Stepped-care Cbt Modelmentioning
confidence: 99%